10‐year anniversary of the European Somnologist examination – A historic overview and critical appraisal. (11th June 2022) - Grote, Ludger; Pevernagie, Dirk; Bruni, Oliviero; Deboer, Tom; Garcia‐Borreguero, Diego; Hill, Elizabeth A.; Penzel, Thomas; Puertas, F. Javier; Wiechmann, Axel; Verspaandonk, Margret; Paunio, Tiina
Summary: The European Somnologist certification programme was developed by the European Sleep Research Society to improve patient care in sleep medicine by providing an independent evaluation of theoretical and practical knowledge. The examination of eligible experts plays a key role in this procedure. A process was started more than 15 years ago to create the European sleep medicine curriculum, eligibility criteria for certification, and sleep centre accreditation criteria. The process was characterised by interdisciplinary collaboration, consensus, and achieving new solutions. During the past 10 years, experience has been gained by the examination and certification of more than 1000 sleep medicine experts from more than 50 countries. The process has continuously been improved. However, as the programme was designed and administered mainly by medical experts in the field, systematic influence from teaching and pedagogic experts was partially underrepresented. The current critical appraisal pinpoints several missing links in the process – mainly as a missing constructive alignment between learning objectives, learning and teaching activities, and the final assessment. A series of suggestions has been made to further improve the ESRS certification programme.